The image of political power in the reign of Nerva, AD 96-98 - Elkins, Nathan T. (Oxford University Press, 2017)
Nerva, who ruled from 18 September AD 96 to 27 January AD 98, left little for the art historian or archaeologist on account of his short reign. In view of the paucity of decorated monuments or other visual evidence, studies of Nerva focus on the historical circumstances governing his reign with respect to the few relevant literary sources. This work, by contrast, takes the entire imperial coinage program issued by the mint of Rome to examine the self-representation, and, by extension, the policies and ideals of Nerva's regime